Manajemen Anestesi Gravida dengan Plasenta Akreta yang dilakukan Seksio Sesarea dengan Transarterial Ballooning - Azman, Radhillah; isngadi, Isngadi (Jurnal Anestesi Obstetri Indonesia, 2024)
Bleeding before (antepartum) and after (postpartum) delivery remains a major contributor to perinatal mortality and maternal morbidity worldwide. Placenta accreta is a cause of maternal morbidity and mortality, recently becoming the most common reason for emergency postpartum hysterectomy. A 35-year-old woman weighing 55 kg, height 151 cm, G3P1101Ab000 at a gestational age of 34-36 weeks, with a history of antepartum bleeding and suspicion of placenta accreta from the ultrasound, is scheduled for pregnancy termination via cesarean section. Before the surgery, a transarterial balloon catheter is inserted, and the estimated blood loss during the operation is around 10,000 ml. In this patient, the choice of general anesthesia is made considering the history of third-trimester bleeding, a high probability index score of 51% for accreta, and the plan for hysterectomy, leading to an anticipated prolonged operation time. Additionally, the risk of significant bleeding during the surgery prompts the selection of general anesthesia for hemodynamic management, and the placement of a catheter balloon is done to anticipate massive bleeding. To obtain a more comprehensive comparison and understanding of estimated blood loss, a comparison with other cases involving catheter balloon procedures before or after surgery is needed.